Correlation between Digital Storytelling and Students' Narrative Writing Text Ability - Akbar, Muhammad diva (JEDLISH : Journal Of Education and English Language Teaching, 2024)
The study explored the correlation between digital storytelling (DST) and students' narrative writing Text Ability, utilizing a quantitative correlational research design. Conducted among 34 eleventh-grade students at SMAN 1 Kramatwatu, the study employed two key instruments: a DST performance test and a narrative writing test. Statistical analyses, including normality, homogeneity, and linearity tests, confirmed the suitability of the data for correlation analysis. The Pearson Product Moment correlation revealed a strong positive relationship (r = 0.851, p < 0.05) between the two variables, indicating that students who excelled in DST also demonstrated superior narrative writing ability. The findings underscored the potential of DST as an innovative educational tool that combines visual and auditory elements to enhance creativity, coherence, and engagement in narrative writing. This study highlights the importance of integrating DST into teaching practices to foster students' writing abilities and overall language proficiency. Future research should explore the implementation of DST across diverse educational contexts to further validate its effectiveness and adaptability.